Maternal GNAS Contributes to the Extra-Large G Protein α-Subunit (XLαs) Expression in a Cell Type-Specific Manner - Cui, Qiuxia; Aksu, Cagri; Ay, Birol; Remillard, Claire E.; Plagge, Antonius; Gardezi, Mina; Dunlap, Margaret; Gerstenfeld, Louis C.; He, Qing; Bastepe, Murat (Frontiers in Genetics, 2021)
GNAS encodes the stimulatory G protein alpha-subunit (Gsα) and its large variant XLαs. Studies have suggested that XLαs is expressed exclusively paternally. Thus, XLαs deficiency is considered to be responsible for certain findings in patients with paternal GNAS mutations, such as pseudo-pseudohypoparathyroidism, and the phenotypes associated with maternal uniparental disomy of chromosome 20, which comprises GNAS. However, a study of bone marrow stromal cells (BMSC) suggested that XLαs could be biallelically expressed. Aberrant BMSC differentiation due to constitutively activating GNAS mutations affecting both Gsα and XLαs is the underlying pathology in fibrous dysplasia of bone. To investigate allelic XLαs expression, we employed next-generation sequencing and a polymorphism common to XLαs and Gsα, as well as A/B, another paternally expressed GNAS transcript. In mouse BMSCs, Gsα transcripts were 48.4±0.3% paternal, while A/B was 99.8±0.2% paternal. In contrast, XLαs expression varied among different samples, paternal contribution ranging from 43.0% to 99.9%. Sample-to-sample variation in paternal XLαs expression was also detected in bone (83.7% to 99.6%) and cerebellum (83.8 to 100%) but not in cultured calvarial osteoblasts (99.1±0.1%). Osteoblastic differentiation of BMSCs shifted the paternal XLαs expression from 83.9±1.5% at baseline to 97.2±1.1%. In two human BMSC samples grown under osteoinductive conditions, XLαs expression was also predominantly monoallelic (91.3% or 99.6%). Thus, the maternal GNAS contributes significantly to XLαs expression in BMSCs but not osteoblasts. Altered XLαs activity may thus occur in certain cell types irrespective of the parental origin of a GNAS defect.